Perancangan Strategi Pemasaran Toko Online Berbasis Bauran Pemasaran untuk Meningkatkan Kinerja Penjualan - Alius, Mutia; Shofia, Alima; Yunas, Barkhia; Domila, Herni (-, 2026)
The rapid growth of e-commerce requires online businesses to implement effective marketing strategies to maintain competitiveness. Salwa Kids, an online store operating on the Shopee platform, experienced a decline in sales in recent months, indicating the need to evaluate its current marketing strategy. This study aims to analyze the implementation of the marketing mix (4P: product, price, place, promotion) and to formulate more effective marketing strategies to improve sales performance. This research employed a descriptive qualitative approach using purposive sampling involving 30 consumers and 1 business owner. Data were collected through interviews, observations, documentation, and questionnaires. Data analysis was conducted using Content Analysis supported by NVivo 12 Plus software. The results indicate that the product aspect holds the highest proportion of discussion (32%), followed by promotion (28%), price (24%), and place (16%). Product quality and comfort are the primary factors influencing purchase decisions. Promotional activities are still focused on discounts and marketplace features, while social media utilization remains limited. Pricing is perceived as affordable but sensitive to discounts, and distribution is effective yet limited to a single platform. The recommended strategies include strengthening product differentiation, optimizing digital promotion through creative content, implementing structured discount programs, and diversifying distribution channels. An integrated 4P strategy is expected to enhance competitiveness and achieve sustainable sales growth for Salwa Kids.